Satellite Techniques and its Possible Application in Foot and Mouth Disease Control in Nigeria: A Review (Global Journal of Science Frontier Research, 2014)
Satellite techniques have been used in disease epidemiology for decades in the western world. However, its application in developing countries like Nigeria is under exploited but highly desirable especially in the livestock sub sector that is heavily laden with numerous diseases of economic value. The economic burden of Bovine Foot and Mouth disease on the livelihood of livestock owners and trade is on increase with the emergence of seemingly more virulent viruses, as evidenced by genetic diversification of serotypes in recent phylogenetic studies. Creating awareness on satellite application especially Geographic Information system (GIS) in Foot and Mouth disease surveillance and control would aid in alleviating the aforementioned negative impact. The purpose of this review is to summarize our current understanding of bioinformatics on its applications to livestock disease control with a chronological review of prevailing scientific tenets and practices as described in scientific veterinary journals and textbooks is as discussed. To promote awareness and use of GIS and other satellite applications in the control of livestock diseases especially Foot and Mouth disease, training and re-training of veterinary personnel in the field of veterinary bioinformatics and satellite techniques is therefore advocated.